Taxonomic notes on the leafhopper genus Phlogothamnus Ishihara (Hemiptera: Cicadellidae: Deltocephalinae), with description of a new species from China - Hassan, Muhammad Asghar; Zhang, Jie; Xing, Jichun (Zootaxa, 2024)
A new leafhopper species Phlogothamnus renhuaiensis sp. nov. is described and illustrated from Guizhou Province, China. An updated identification key for the adult male Phlogothamnus species is provided, and a global distribution map showing the geographic distribution of all species is also provided. A cumulative checklist of 10 Phlogothamnus species including the basionym, localities of type materials, type depositories, and updated distribution data is also presented. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).